EFFECT OF RECYCLED MATERIALS AND HYBRID FIBERS ON THE PROPERTIES OF SELF-COMPACTING CONCRETE - Dawood, Eethar; Salah Fathy Al-heally, Maysam (Journal of Applied Engineering Science, 2021)
Self-compacting concrete (SCC) has many properties comparing to conventional concrete and represents a good choice towards sustainability. The use of different recycled materials contributes to seize the negative impact of huge amount of waste on the ecosystem. In this study, locally available materials have been used as partially cement replacements. Such materials including ceramic waste powder (CWP) and glass powder (GP) in addition to fly ash with total cement replacement of 30%(12%CWP+8%GP+12%Fly ash) have been found to increase the compressive strength by about 7% compared to the control SCC. Normal aggregate was replaced by recycled aggregate with different recycled aggregate which are Recycled Concrete (RC), Crushed red brick (REB) and Crushed ceramic (CER.) The percentages of replacements are: 25%, 50%, 75% and 100%, for each type of aggregate. The results show that the increase of the amount of recycled aggregates decreases the strength properties of SSC and effect on workability of SSC also the result show a reduction in oven dry density. The combination of different type of recycled aggregate shows a reduction in SSC strength. The use of fibers shows better performance of SSC compared to combination aggregate mix without fiber but reduce the workability of SCC. However, the fiber content of 1.0% shows the best result of the mechanical properties, whereas, fiber content up to 1.5% affects negatively on concrete properties. The use of hybrid fiber also increases the strength properties of concrete..